Brief History of the Constitutional Court of the Czech and Czechoslovak Republic and its role in upholding the rule of law - Stanislav Balík (Journal on European History of Law, 2024)
The article provides a historical overview of the Constitutional Court in the Czech lands from its establishment in 1920 until the present day. The author, a judge of the Constitutional Court, acknowledges the debt to honour the institution's history and discusses its development and periods of activity and inactivity. The jurisdiction, composition, and decision-making activities of the Constitutional Court are compared across different periods, highlighting the expansion of its powers and professionalisation over time. The article also touches on the role of the Constitutional Court in protecting human rights and its growing importance in post-communist Czech society. The author emphasises the necessity of an independent Constitutional Court for establishing a legal state and concludes by expressing satisfaction with the current state of the Czech Republic's constitutional judiciary.